2000
DOI: 10.1136/jech.54.5.394
|View full text |Cite
|
Sign up to set email alerts
|

Low immunisation uptake: Is the process the problem?

Abstract: Objective-To examine mothers' satisfaction with the process of immunisation and its possible contribution to suboptimal immunisation uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…It showed that 82.4 % of mothers who had adequate knowledge have their children completely immunized while only 56% of mothers with inadequate knowledge had their children completely immunized. There was no association between the knowledge and completeness of immunization [30][31][32][33][34]. This could be explained that the whole maternal satisfaction about quality have more than one element other than knowledge such as doctor pt relationship, staff attitude, cost, and waiting time, and despite low knowledge score but remains the fact that source of information when it is given by a physician is better than other source from client perspective, and the only motive to attend for vaccination program is the maternal perceived seriousness of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…It showed that 82.4 % of mothers who had adequate knowledge have their children completely immunized while only 56% of mothers with inadequate knowledge had their children completely immunized. There was no association between the knowledge and completeness of immunization [30][31][32][33][34]. This could be explained that the whole maternal satisfaction about quality have more than one element other than knowledge such as doctor pt relationship, staff attitude, cost, and waiting time, and despite low knowledge score but remains the fact that source of information when it is given by a physician is better than other source from client perspective, and the only motive to attend for vaccination program is the maternal perceived seriousness of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…From these 54 studies, 15 met the inclusion criteria and were included in the systematic review. Of these 15 studies, 8 used semistructured interviews (a total of 201 participants) [17][18][19][20][21][22][23][24], 5 used focus groups [23,[25][26][27][28] (total n 5 236), and 2 used both interviews and focus groups [29,30] (total n 5 107). Studies using both interviews and focus groups were analyzed according to their primary reported methods (which in these two instances was the semistructured interview).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…The studies were conducted in five different countries: six were from the United States [22,23,[25][26][27]30], three from the United Kingdom [20,28,31], two from Canada [21,24], two from Australia [17,19], one from Ireland [18], and one from New Zealand [27,29]. Eight studies examined a variety of attitudes toward vaccines, including barriers [18,[21][22][23]25,[29][30][31], and seven studies sought only to examine barriers to obtaining vaccination [17,19,20,24,[26][27][28]. Table 2 summarizes study and participant characteristics.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Of the 15 qualitative studies included in our systematic review, 8 studies used semistructured interviews (a total of 201 participants) [9][10][11][12][13][14][15][16], 5 used focus groups [15,[17][18][19][20] (total n ϭ 236), and 2 used both interviews and focus groups [21,22] (total n ϭ 107). The data represents 544 participants in total.…”
Section: Qualitative Studiesmentioning
confidence: 99%